Penerapan Model Contextual Teaching And Learning (CTL) Dalam Pembelajaran Ipas Pada Siswa Kelas V Sekolah Dasar - Tamara Adinda; Naira Nazira; Seri Hartati (Journal of Sustainable Education, 2026)
This study aims to analyze the application of the Contextual Teaching and Learning (CTL) learning model in Natural and Social Sciences (IPAS) learning for fifth-grade elementary school students and examine its impact on improving students' conceptual understanding, learning activities, and critical thinking skills. This study uses a literature study method by reviewing various relevant library sources, such as scientific journals, reference books, and academic documents related to the application of CTL in elementary schools. The data collection process was carried out through the stages of literature identification, selection of appropriate articles, content analysis, and synthesis of previous research results. Data analysis was conducted descriptively qualitatively to obtain a comprehensive picture of the effectiveness of the CTL model in IPAS learning. The results of the study indicate that the application of the CTL model has a positive impact on the learning process and outcomes. This model is able to improve students' conceptual understanding, activities, learning motivation, and critical thinking skills by connecting the material to real-life contexts. However, there are obstacles such as limited learning resources, teacher readiness, and learning time. Therefore, careful planning and support from various parties are needed for optimal implementation of CTL.